دراسة التكامل المشترك بين مخرجات التعليم العالي والنمو الاقتصادي في سورية - أحمد، طالب; نجار، كمال حكمت (جامعة تشرين, 2023)
هدف البحث إلى استخدام طريقة التكامل المشترك بين مخرجات التعليم العالي والنمو الاقتصادي في سورية من خلال تطبيق نماذج ARDL، وهل توجد علاقه توازنية طويلة الأجل بين هذه المؤشرات؟. وكانت أهم نتائج الدراسة: هناك علاقه قصيرة الأجل وطويلة الأجل لخريجي الجامعات الحكومية وخريجي المعاهد التقنية على النمو الاقتصادي، بينما لا توجد علاقة طويلة الأجل بين خريجي الدراسات العليا وخريجي المعاهد العليا على النمو الاقتصادي حيث توجد علاقه قصيرة الأجل بين هذه المتغيرات، واستنادا لنموذج تصحيح الخطأ تفسر مؤشرات خريجي التعليم العالي 0.42% من تغيرت النمو الاقتصادي على المدى البعيد. The research aimed to use the method of joint integration between the outputs of higher education and economic growth in Syria through the application of ARDL models, and is there a long-term equilibrium relationship between these indicators? The most important results of the study were: There is a short-term and long-term relationship for graduates of public universities and graduates of technical institutes on economic growth, while there is no long-term relationship between graduates of postgraduate studies and graduates of higher institutes on economic growth, as there is a short-term relationship between these variables, and based on the error correction model Indicators of higher education graduates explain 0.42% of the changes in economic growth in the long run.
Keywords: التنمية الاقتصادية -- التكامل المشترك -- السلاسل الزمنية -- خريجو الجامعات -- سوريا